Universal Justice in QS. Al-Mā’idah Verse 8: A Fazlur Rahman Hermeneutical Approach and a Critique of Global Human Rights Selectivity in the Palestinian Case - Mas'odi Mas'odi; Moh Zahid; Muhammad Khairul Anam bin Misdun (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
his study examines the principle of universal justice in Qur’anic verse QS. Al-Mā’idah 8 through Fazlur Rahman’s double movement hermeneutical approach and its relevance to the issue of global Human Rights (HR) bias in the case of Palestine. The verse emphasizes the obligation to uphold justice for all people, including adversaries, and rejects any form of injustice driven by hatred, prejudice, or political interests. This research employs a qualitative method using library-based analysis. The findings indicate that although various international human rights organizations have documented serious violations committed by Israel against the Palestinian people, global responses—particularly from major powers such as the United States—remain selective and politically motivated. This situation reveals a significant disparity between the ideal principles of universal human rights and their actual implementation in geopolitical practice. The study concludes that the Qur’anic principle of justice, when interpreted through Rahman’s hermeneutics, provides a strong ethical framework for critiquing such double standards and for promoting a more consistent, impartial, and humane human rights paradigm in support of justice for Palestine.